PERSEPSI KUALITAS LAYANAN MUSEUM SEBAGAI SARANA EDUKASI MASYARAKAT (STUDI KASUS: MUSEUM GUNUNG API MERAPI YOGYAKARTA) - Kiswantoro, Amin; Damiasih, Damiasih (Kepariwisataan: Jurnal Ilmiah, 2018)
The purpose of this study is to determine the development of agrotourism Kampoeng Kopi Banaran and to analyze employee performance in supporting the development of agrotourism in Kampoeng Kopi Banaran, in Semarang Regency. In particular the goal is to find out how management efforts in developing agrotourism Kampoeng Kopi Banaran, management of human resources, employee performance in supporting the development of agrotourism.The study is mixed methods using 56 respondents as samples. While data analysis in this research using multiple regression analysis using F test and t test. The results of the data analysis of socio-demographic explain that influence on the performance showed that age, gender, education, family status, employment status and work experience positively affect employee performance. While F-test states that jointly age, gender, education, family status, employment status and work experience affect the performance. t test in this research shows there is no significant influence of gender on the performance, no significant influence of the family status on the performance. The conclusions of this study are that there is a positive and significant influence of socio-demographic on emplyoee performance and there is a positive and significant influence between employee performance against agrotourism understanding in Kampoeng Kopi Banaran. Keywords: merapi volcano museum, MGM, tourist perception, service quality